1998
DOI: 10.1021/ie970469b
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigation of Hydrous TiO2 Precipitates and Their Aging Products by X-ray Diffraction, Atomic Force Microscopy, and Transmission Electron Microscopy

Abstract: The structure of TiO2 hydrates is studied by X-ray diffraction, atomic force microscopy (AFM), and transmission electron microscopy (TEM). The samples prepared by NH4OH precipitation from an aqueous TiCl4 solution are amorphous or partially crystalline. They consist of a mixture of distorted anatase and brookite crystallites, each having a diameter of 20 nm. The sample prepared by thermal hydrolysis from a titanium oxide sulfate solution was totally crystalline, composed only of distorted anatase crystallites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Water molecules are directly bonded to the terminal OH groups by hydrogen bonding. These water molecules link to the other water molecules via hydrogen bonds . Hence, the titania gel in this study can be called hydrous titania gel and described as TiO 2 · n H 2 O, or more precisely as TiO 2− x (OH) 2 x ·( n − x )H 2 O.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Water molecules are directly bonded to the terminal OH groups by hydrogen bonding. These water molecules link to the other water molecules via hydrogen bonds . Hence, the titania gel in this study can be called hydrous titania gel and described as TiO 2 · n H 2 O, or more precisely as TiO 2− x (OH) 2 x ·( n − x )H 2 O.…”
Section: Resultssupporting
confidence: 68%
“…These water molecules link to the other water molecules via hydrogen bonds. [19][20][21][22] Hence, the titania gel in this study can be called hydrous titania gel and described as TiO 2 ÁnH 2 O, or more precisely as TiO 2Àx (OH) 2x Á(nÀx)H 2 O. The n value depends on the extent of polymerization of Ti (OH) 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The formation of an admixture of brookite in anatase in aged samples obtained from alkaline media has been already noticed in Ref. [16]. The crystallite size determined by means of the Scherrer method gives R cryst = 3 nm (Table 1).…”
Section: Resultssupporting
confidence: 55%
“…Characteristics peaks were noted at higher concentrations of nHA rather than at lower concentrations of nHA. It is noteworthy that the crystalloid characteristics were masked by gelatin at low concentrations of nHA, indicating that gelatin could reduce the crystalloid properties (Jalava et al, ). Therefore, our results were similar to results reported in another study, which revealed that chitosan could reduce the crystal growth of nHA (Dumont et al, ).…”
Section: Resultsmentioning
confidence: 99%